MODEL PENGELOLAAN N, P DAN K PADA TANAH SAWAH DI KECAMATAN JATISRONO, WONOGIRI - Aisyiyah Amini; Sudjono Utomo; Mujiyo Mujiyo (Faculty of Agriculture, Universitas Sebelas Maret, 2010)
Title : N, P, and K Management Model for Paddy Soils in Subdistrict Jatisrono, Wonogiri. Available of N, P and K nutrient at paddy soil of Sub district Jatisrono, Regency Wonogiri very low cause farmer fertilizer application, land morphology, and climate. The purpose of this research is to prove that relationship model endogen and exogenous variable can be used as reference in N, P and K management for paddy soil. This research was conducted in Sub district Jatisrono, Regency Wonogiri at February until June 2008. This research is descriptive explorative and functional relationship research. The variables approach by field survey and supported laboratory analysis of the soil chemical and physical properties, use statistical analysis stepwise regression, simple Correlation test and regression analysis. The result of this research show that model which have been tested can be use as reference in N, P and K management for paddy soil in Sub district Jatisrono, Regency Wonogiri, while its model is total soil N is = 0.939 + 0.424 KPK + 0.006 Fertilizer Type, Soil Available P = 45.9 – 3.9 pH + 2.38 fertilizer Dose, Soil Available K = - 0.016 + 0.0482 pH – 0.0010 organic substance. Keywords: N, P, and K Management Model, Paddy Soils